Identity, truth and value : essays for David Wiggins - Lovibond, Sabina; Wiggins, David; Williams, S. G. (Blackwell, 1996)
This collection of essays was presented to David Wiggins to mark his 60th birthday and his accession to the Wykeham Chair of Logic at Oxford. The contributors, who include both long--established and younger writers, take up some of the many important philosophical debates on which Wiggins has made an impact. Their chosen topics range from ancient philosophy to contemporary questions in ethics, metaphysics and the theory of meaning. An attractive feature of the volume is that it contains Wigginsa s comments on each of the papers, and so offers an accessible guide to his present thinking.